Spiritual Experience and Character Formation: Finding Balance in Pentecostal Spiritual Formation Tradition - Sugiri, Widjaja (LPPM - Sekolah Tinggi Teologi Indonesia Jakarta, 2025)
The article explores the imbalance in Pentecostal spiritual formation, where the focus on personal experiences with the Holy Spirit, such as speaking in tongues and healing, often overshadows the importance of deep theological education, spiritual disciplines, and character formation. The aim is to highlight the gaps in spiritual formation within Pentecostalism and propose ways to integrate emotional experiences with doctrinal understanding for a more holistic spiritual growth. The article uses a theoretical approach, reviewing existing theological perspectives and spiritual practices, referencing scholars like Anderson, McGrath, and Banda. The results reveal several key issues: a lack of theological depth, neglect of regular spiritual practices, and insufficient emphasis on Christian character and ethics. It also points to the underdeveloped role of community and intergenerational learning in spiritual formation. The contribution of the article is in proposing a balanced approach to spiritual growth that combines emotional experiences with solid theology, regular spiritual practices, ethical living, and strong community involvement, ultimately offering a framework for more sustainable spiritual maturity within Pentecostalism. Artikel ini membahas ketidakseimbangan dalam pembentukan rohani Pentakosta, di mana penekanan pada pengalaman pribadi dengan Roh Kudus—seperti berbahasa roh dan penyembuhan—sering kali mengesampingkan pentingnya pendidikan teologis yang mendalam, disiplin rohani, dan pembentukan karakter. Tujuannya adalah untuk menyoroti kesenjangan dalam pembentukan rohani di kalangan Pentakosta dan mengusulkan cara untuk mengintegrasikan pengalaman emosional dengan pemahaman doktrinal guna mencapai pertumbuhan rohani yang lebih holistik. Artikel ini menggunakan pendekatan teoretis dengan meninjau perspektif teologis dan praktik rohani yang ada, serta merujuk pada para sarjana seperti Anderson, McGrath, dan Banda. Hasilnya mengungkap beberapa masalah utama: kurangnya kedalaman teologi, pengabaian terhadap praktik rohani yang teratur, dan penekanan yang tidak memadai pada karakter serta etika Kristen. Artikel ini juga menyoroti peran komunitas dan pembelajaran antar generasi yang belum berkembang dengan baik dalam pembentukan rohani. Kontribusi utama artikel ini terletak pada usulannya untuk menciptakan pendekatan seimbang dalam pertumbuhan rohani yang memadukan pengalaman emosional dengan teologi yang kokoh, praktik rohani yang teratur, kehidupan etis, serta keterlibatan aktif dalam komunitas. Pendekatan ini pada akhirnya menawarkan kerangka bagi kematangan rohani yang lebih berkelanjutan dalam tradisi Pentakosta.